The power of ethical investment in the context of political uncertainty - Lucía Morales; Amparo Soler-Domínguez; James Hanly (Journal of Applied Economics, 2019)
In this paper we analyse a set of socially responsible investment (SRI) indices against their conventional counterparts in the US context. Using a data set that spans the Obama and Trump administrations, we aim to identify whether performance and volatility patterns differ when markets are exposed to political uncertainty and the Global Financial Crisis (GFC). The findings suggest that SRI indices underperform conventional indices, and that the S&P 500 has a significant impact on their behaviour. The CBOE's Volatility Index (VIX), the US Equity Related Economic Uncertainty Index (EEUi) and the impact of the economic policy uncertainty index (EPUi) are used to consider market volatility and political uncertainty, with VIX emerging as the best indicator to capture market uncertainty. The study signals a positive and significant impact on SRI indices during the first hundred days of the Obama administration with a lack of significant findings for the Trump administration for the period of study. The results for implied volatility reveal similar patterns across all indices.
Keywords: 330; causality domain; economic policy uncertainty; global financial crisis; implied volatility; Socially responsible investment